Obstetric and neonatal conditions and associations with early skin-to-skin contact – a cross-sectional study - Joan Neergaard Larsen; Helena Hansson; Porntiva Poorisrisak; Laura E. Navne; Ane Lilleøre Rom; Hanne K. Hegaard; Jette Led Sørensen; Ragnhild Maastrup (BMC Pregnancy and Childbirth)
Abstract Background Mother-infant separation during postpartum care is common when either the infant or the mother requires specialized treatment, often disrupting skin-to-skin contact (SSC) and closeness for parents and infants. SSC promotes parent-infant bonding and has numerous short- and long-term benefits. However, challenges in implementation remain, especially in the highly specialized setting. We aimed to describe the frequency of obstetric and neonatal conditions in mother-infant pairs requiring postnatal care and to examine potential associations between these conditions and early SSC within six hours after birth with mother or co-parent. Methods This cross-sectional study included mother-infant pairs admitted to the Departments of Obstetrics and Neonatology. We collected data from medical records and questionnaires. We used descriptive statistics to analyze the frequency of conditions, and binomial generalized linear models were applied to analyze associations between selected conditions and early SSC. Results We included 186 mothers with a median age of 32, of which 22.6% had chronic medical conditions, 54.8% underwent cesarean section, and 17.7% developed preeclampsia and/or HELLP. The mothers’ 208 infants had a median gestational age of 33.36 weeks, 8.3% had an Apgar score of less than seven after 5 min, and 86.1% required respiratory support. Having an emergency or an elective cesarean section lowered the odds of early SSC compared to women without cesarean section (adjusted odds ratio (aOR) 0.19, 95% confidence interval (CI) 0.07; 0.46 and aOR 0.11, 95% CI 0.03; 0.36 respectively). All preterm infants had lower odds of early SSC compared to term infants, and the extremely preterm infants had the lowest odds (aOR 0.01, 95% CI: 0.00–0.04). Other neonatal conditions negatively associated with early SSC included Apgar scores less than seven after 5 min and need for respiratory support (aOR 0.15, 95% CI: 0.03–0.7 and aOR 0.07, 95% CI: 0.00–0.39). Conclusions The frequency of obstetric and neonatal conditions in mother-infant pairs is substantial, reflecting how mothers and infants often face different conditions simultaneously. We identified negative associations between cesarean section, prematurity, Apgar scores less than seven after 5 min, need for respiratory support, and the initiation of early SSC within six hours after birth.